Predictive Risk Factors and Occupational Impact of Self-Perceived Voice Problems in Preschool-Kindergarten versus First- to Sixth-Grade Teachers - Kyriakou, Kyriaki; Theodorou, Elena; Petinou, Kakia; Phinikettos, Ioannis (My University, 2022)
Aim: The aim of this investigation was to complete a further analysis of existing data to compare risk factors of voice problems as well as create a hierarchical ranking of risk factors in preschool-kindergarten and 1st- to 6th-grade teachers in order to develop a voice hygiene program and prioritize its goals for each group of teachers. Methods: An online survey was completed by 148 preschool-kindergarten and 301 1st- to 6th-grade public school teachers. Participants were divided into four groups, preschool-kindergarten and 1st- to 6th-grade teachers with no self-perceived voice disorders and preschool-kindergarten and 1st- to 6th-grade teachers with self-perceived voice disorders. A χ2 test and a multivariate logistic regression model were used to examine the differences in answers between the preschool-kindergarten teachers with and without voice disorders and the 1st- to 6th-grade teachers with and without voice disorders and to identify the most important predictors. Results: The significant predictors for preschool-kindergarten teachers are frequently or sometimes continuing to talk after a breath cycle and being exposed to an excessive or a lot of noise generated in the classroom. The significant predictors for 1st- to 6th-grade teachers include having short breaks between classes and continuing to talk frequently after a breath cycle. Conclusions: Job-related risk factors in preschool-kindergarten and in 1st- to 6th-grade teachers may vary. Therefore, a preventative vocal hygiene education program specifically tailored for each population of teachers is suggested.
Keywords: Occupational impact; Predictive risk factors; Teachers; Voice problems